Maksim Leonidovich Golovaha - Ukrainian Association of Orthopedic Traumatologists, - (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to the 50th anniversary of the orthopedist-traumatologist of the higher medical category, the head of the department of traumatology and orthopedics of Zaporizhzhya State Medical University, Doctor of Medical Sciences, Professor Golovaki Maxim Leonidovich.